Wadowiczanie w Krakowie. Kariera akademicka i kościelna Marcina Wadowity i jego poprzedników - Graff, Tomasz (Analecta Cracoviensia, 2011)
The article discusses the mentions of citizens of Wadowice who, like Karol Wojtyla, followed church of academic carreers. The author examines the period from the close of the Middle Ages till the times of a renown theologian from Wadowice - Marcin Wadowita (died in 1641). He tries to find all the students from Wadowice studying in Cracow at that time. The author, besides the most important facts from the life of Martin Wadowita, describes so far unknown portrait of the professor to be found in Karmelitę Monastery in Krakow. Apart from Wadowita, the article also describes Jakub from Wadowice (died in 1495), a provost in the monastery of canons regular in Kazimierz.